2009
DOI: 10.1111/j.1742-1241.2008.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral arterial disease in high-risk patients using ankle-brachial index in general practice: a cross-sectional study

Abstract: Aims:The deleterious nature of peripheral arterial disease (PAD) is compounded by a status of underdiagnosed and undertreated disease. We evaluated the prevalence and predictive factors of PAD in high-risk patients using the ankle-brachial index (ABI).Methods:The ABI was measured by general practitioners in France (May 2005–February 2006) in 5679 adults aged 55 years or older and considered at high risk. The primary outcome was prevalence of PAD (ABI strictly below 0.90).Results:In all, 21.3% patients had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
(42 reference statements)
1
35
1
2
Order By: Relevance
“…(17,18) According to our results, older patients, men, patients with diabetes mellitus or patients with renal insufficiency have a higher risk to present with critical limb ischaemia. Health professionals should be aware of the causes leading to such a highly compromised situation.…”
Section: Discussionmentioning
confidence: 64%
“…(17,18) According to our results, older patients, men, patients with diabetes mellitus or patients with renal insufficiency have a higher risk to present with critical limb ischaemia. Health professionals should be aware of the causes leading to such a highly compromised situation.…”
Section: Discussionmentioning
confidence: 64%
“…KONIN [8] had found that the total hypercholesterolemia was correlated with occurred of the PAD in 40.9% of the cases. CACOUB [15] had found 26.9% of hypercholesterolemia among subjects with PAD in his population of study with a statistically significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…ROUL [16] had found a prevalence of 40% of PAD among coronary patients. In CAPRIE study, including nearly 20.000 patients, 15.2% of the patients with a coronary pathology were with lower limb arteriopathy [17]. In the PARTNERS (PAD awareness, Risk and Treatment: new Resources for Survival) study, 16% among the coronary patients presented with chronical obstructive arterial disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Cacoub et al observed that patients aged 74 and above have lower ABI values and a higher risk for peripheral artery disease [8].…”
Section: Discussionmentioning
confidence: 99%